Implementation of Watershed Based Image Segmentation Algorithm using Distance Transform for Grid Computing (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
A new method for image segmentation using watershed transform algorithm is presented in this paper. It takes advantage of the fact that the proposed algorithm produced good results even if the same parameters are used for the standard segmentation algorithm. The proposed segmentation algorithm will be very effective for grid computing as it seems to possess specific tasks of image information and detection in order to obtain a detailed and accurate image analysis.